Green Banking Practices and Green Financing of Listed Deposit Money Banks in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examined the nexus between green banking practices and green financing sources of listed deposit money banks in Nigeria. The study anchored on the institutional theory and cross sectional survey research design was adopted with a population consisting of listed banks in Nigeria. The study used stratified random sampling of seven hundred and fifty (750) bank employees with questionnaire as the primary source of data collection from the respondents while only five hundred (500) were used for data analysis using univairate, bivariate and multivariate methods of data analysis. The results from the regression analysis disclosed that banks’ employee-related practices of green banking positively and significantly influence sources of green financing of deposit money banks in Nigeria; banks’ daily operations-related practices of green banking positively and significantly affect sources of green financing of deposit money banks in Nigeria; banks’ customers-related practices of green banking positively but significantly influence sources of green financing of deposit money banks in Nigeria; banks’ policy-related practices of green banking positively and significantly influence sources of green financing of deposit money banks in Nigeria and banks’ green investment related practices of green banking positively and significantly impact on sources of green financing of deposit money banks in Nigeria. Consequently, on the basis of the findings the study concluded that green banking practices positively influences the sources of green financing of deposit money banks in Nigeria. Therefore, the study recommends amongst others that banks’ in Nigeria should adopt contemporary banking practices that are ecofriendly as a means of enhancing the sources of green financing in Nigeria.